Penerapan Model Waterfall Pada Sistem Informasi Pembelian Bahan Baku Roti - Apriana, Veti; Mutiah, Septiany Khoirum (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2018)
Computers are tools that are created to facilitate human work, Zabidhi Bread Store requires once a system that supports and provide convenience for its employees, especially the purchase. The procurement of raw materials and auxiliary materials is handled by the warehouse and production sections under direct supervision by the owner of the company. Companies must be able to hold and manage raw materials with good and quality to support the smoothness of the production process so that later products produced have high selling value. For that reason the author tries to make Software Engineering Purchase of Raw Materials In Zabidhi Bread Bakery. Toko Zabidhi Bread is a company engaged in the food industry. The current system still uses the system manually, making it possible at the time of the process there was an error in recording. Raw material information system using waterfall method is the best solution to handle and minimize errors that occur in this company, as well as with a computerized system can be achieved a more effective and efficient activities in supporting activities in this company.